1999
DOI: 10.1088/0266-5611/15/1/028
|View full text |Cite
|
Sign up to set email alerts
|

On the regularization of nonlinear ill-posed problems via inexact Newton iterations

Abstract: Inexact Newton methods for the stable solution of nonlinear ill-posed problems are considered. The corresponding inner scheme can be chosen to be any linear regularization with a sufficient modulus of convergence. The regularization property of these Newton-type algorithms is verified, that is, the iterates converge to a solution of the nonlinear problem with exact data when the noise level tends to zero. Moreover, convergence rates are given. Finally, implementation issues are discussed and the algorithm is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 18 publications
(37 reference statements)
2
120
0
1
Order By: Relevance
“…Our numerical experiments (see Sect. 7) showed that the parameter selection by Rieder [16] yields good results.…”
Section: Convergence Properties: the Discrete Casementioning
confidence: 99%
See 3 more Smart Citations
“…Our numerical experiments (see Sect. 7) showed that the parameter selection by Rieder [16] yields good results.…”
Section: Convergence Properties: the Discrete Casementioning
confidence: 99%
“…The first example is taken from [16]. We aim at identifying the non-negative coefficient u = u(ξ, η) in the two-dimensional elliptic problem −Δy + uy = f in Ω y = g on ∂Ω (7.1) from the knowledge of the solution y = y(ξ, η) in Ω = (0, 1) 2 .…”
Section: Parameter Identification In Elliptic Pdesmentioning
confidence: 99%
See 2 more Smart Citations
“…This class has been introduced and named REGINN (REGularization based on INexact Newton iteration) by the second author [14]. Each of the REGINN-methods consists of two components, the outer Newton iteration and the inner scheme providing the increment by regularizing the local linearization.…”
mentioning
confidence: 99%